Democracy and Institutional Political Subjectness: Comparative Study for Europe and Central Asia - Natalina, Nataliia (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
Why did the registration of the Gals for Gals name as a trademark and the publication of the Constitutional Tribunal’s ruling stop the largest protest movements for women’s rights in democratic Poland despite unaccomplished goals? What was the source of the 2018 and 2021 demobilization acts and subsequent waves of non-mobilization? Drawing on the theory of moral injury and narrative research methodology, this article aims to account for the determinants of the Gals for Gals’ and the All-Poland Women’s Strike’s demobilization and the lack of mobilization. The main argument is that during the fight for women’s rights, a part of Polish society involved in civic activity experienced two severe traumas. Each of the two waves of mobilization ended in a moral injury development. In both cases, a moral injury involved the loss of trust in self and others. Moreover, in both cases, the moral injuries were so severe that they turned out long-lasting. At the stage of the cognitive dissonance, there were no attempts to resolve it. In other words, activists did nothing to prevent cognitive dissonance from turning into a moral injury. In the first case, it may indicate the organizational and emotional immaturity of activists. In turn, the second case may indicate the weakening of civil society, building Poland’s political culture of withdrawal and submission.

Dlaczego rejestracja nazwy Dziewuchy Dziewuchom jako znaku towarowego i publikacja orzeczenia Trybunału Konstytucyjnego spowodowały zakończenie aktywności przez największe ruchy protestu na rzecz praw kobiet w demokratycznej Polsce i to pomimo nieosiągnięcia celów? Jakie były źródła demobilizacji z 2018 r. i 2021 r. i kolejnych fal braku mobilizacji? Opierając się na teorii krzywdy moralnej i metodologii badań narracyjnych, artykuł ten ma na celu wyjaśnienie determinant demobilizacji i braku mobilizacji Dziewuch i Ogólnopolskiego Strajku Kobiet. Głównym argumentem jest to, że podczas walki o prawa kobiet część polskiego społeczeństwa zaangażowana w działalność obywatelską doznała dwóch poważnych traum. Każda z dwóch fal mobilizacji zakończyła się masowym poczuciem krzywdy moralnej. W obu przypadkach pojawienie się krzywdy moralnej wiązało się z utratą wiary w siebie i innych. Co więcej, w obu przypadkach była ona tak poważna, że okazała się długotrwała. Na etapie pojawienia się dysonansu poznawczego nie podejmowano prób jego rozwiązania. Innymi słowy, aktywiści nie zrobili nic, aby zapobiec przekształceniu dysonansu poznawczego w trwałe poczucie moralnej krzywdy. W pierwszym przypadku może to wskazywać na niedojrzałość organizacyjną i emocjonalną działaczy. Z kolei drugi przypadek może być oznaką słabnięcia społeczeństwa obywatelskiego, tworzenia się coraz większego obszaru kultury politycznej wycofania i uległości w Polsce.
Demokracja i instytucjonalna subiektywność polityczna: studium porównawcze dla Europy i Azji Środkowej
Keywords: political subjectness; institutions; government effectiveness; democracy; subiektywność polityczna; instytucje; skuteczność rządu; demokracja